Solid electrolyte, method for producing solid electrolyte, and battery
Patent Information
- Application Number
- JP2023511229
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-30
- Filing Date
- 2022-03-28
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2042-03-28
Smart Images

Figure 0007637841000003 
Figure 0007637841000004 
Figure 0007637841000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid electrolyte and a battery. [Reference to Related Applications] This application claims the benefit of priority from Japanese Patent Application JP2021-57224, filed on March 30, 2021, the entire disclosure of which is incorporated herein by reference. [Background technology]
[0002] In recent years, with the development of portable devices such as personal computers and mobile phones, the demand for batteries as their power sources has increased significantly. In batteries used for such purposes, an organic electrolyte solution in which an electrolyte is dissolved in a flammable organic solvent has been used as a medium for transferring ions. In batteries containing an organic electrolyte solution, there is a possibility that safety problems may occur.
[0003] To solve these problems and ensure essential safety, development of all-solid-state batteries that use solid electrolytes instead of organic electrolytes is underway. Because solid electrolytes are non-flammable materials, lithium (Li) ion batteries with high safety can be realized.
[0004] In addition, some solid electrolytes, such as sulfide-based materials, are widely known to react with moisture to generate hydrogen sulfide gas. On the other hand, oxide-based solid electrolytes that do not generate gas such as hydrogen sulfide are also being developed widely, but the lithium ion conductivity of these materials is lower than that of sulfides, making it difficult to improve battery output (extract large current). Therefore, R. Miyazaki and H. Maekawa have published "Li + In "Li3AlF6 Mechanically Milled with LiCl" (ECS Electrochemistry Letters, 2012, Vol. 1, No. 6, pp. A87-A89), a solid electrolyte with improved lithium ion conductivity was developed by mechanically milling Li3AlF6 and LiCl.
[0005] By the way, according to FIG. 1 of the above-mentioned Document 1, as the temperature increases, the lithium ion conductivity of the solid electrolyte increases. However, when the temperature exceeds 120 ° C, the lithium ion conductivity significantly decreases. Therefore, a solid electrolyte having high lithium ion conductivity and high temperature stability is required.
Summary of the Invention
[0006] The present invention is directed to a solid electrolyte, and an object thereof is to provide a solid electrolyte having high lithium ion conductivity and high temperature stability.
[0007] The solid electrolyte according to a preferred embodiment of the present invention uses values a to f greater than 0, and the composition formula is Li a+d M b X c A e O f and contains as a main component the components represented by (where M is an element that becomes trivalent as a cation, X is a halogen element, and A is a sulfur element or a phosphorus element), 0.8c ≦ (a + 3b) ≦ 1.2c, and 1.6f ≦ (d + n × e) ≦ 2.4f (where when A is a sulfur element, n is 4 or 6, and when A is a phosphorus element, n is 5) is satisfied.
[0008] According to the present invention, a solid electrolyte having high lithium ion conductivity and high temperature stability can be provided.
[0009] Preferably, in the composition formula, 0 < e / (c + e) ≦ 0.5 is satisfied.
[0010] Preferably, in the composition formula, 0.1a ≦ 3b ≦ 10a is satisfied.
[0011] Preferably, in the composition formula, A is a sulfur element and 0.8d ≦ 2e ≦ 1.2d is satisfied, or A is a phosphorus element and 0.8d ≦ e ≦ 1.2d is satisfied.
[0012] Preferably, in the composition formula, A is elemental sulfur and n is 6. Preferably, in the composition formula, M is elemental aluminum and X is elemental fluorine.
[0013] Preferably, in the solid electrolyte, the half width of a peak detected in a 2θ range of 20 to 25° in measurement with an X-ray diffractometer using CuKα radiation is 0.4° or more.
[0014] The present invention is also directed to a method for producing a solid electrolyte. A method for producing a solid electrolyte according to a preferred embodiment of the present invention comprises the steps of: a) forming a solid electrolyte having a composition formula of Li a M b X c And Li d A e O f (wherein M is an element that becomes trivalent as a cation, X is a halogen element, A is elemental sulfur or elemental phosphorus, a to f satisfy 0.8c≦(a+3b)≦1.2c and 1.6f≦(d+n×e)≦2.4f, and when A is elemental sulfur, n is 4 or 6, and when A is elemental phosphorus, n is 5); and b) preparing a compound represented by the formula: a M b X c and Li d A e O f and subjecting the resultant to mechanical milling. a M b X c and Li d A e O f The amount of Li in the total amount of d A e O f The proportion of the substance amount is 85% or less.
[0015] Another preferred embodiment of the method for manufacturing a solid electrolyte according to the present invention comprises: a) a step of preparing a first compound which is LiX, a second compound which is MX3, and a third compound which consists of Li, A, and O (where X is a halogen element, M is an element that becomes trivalent as a cation, and A is a sulfur element or a phosphorus element); and b) a step of subjecting the first compound, the second compound, and the third compound to mechanical milling treatment. In the step a), when the molar ratios of Li, M, X in the mixture of the first compound and the second compound, and Li, A, O in the third compound are represented as a:b:c:d:e:f using values a to f greater than 0, 0.8c ≦ (a + 3b) ≦ 1.2c and 1.6f ≦ (d + n×e) ≦ 2.4f (where when A is a sulfur element, n is 4 or 6; when A is a phosphorus element, n is 5) are satisfied, and further 0 < e / (c + e) ≦ 0.5 is satisfied.
[0016] The present invention is also directed to a battery. A battery according to a preferred embodiment of the present invention includes a positive electrode, a negative electrode, and an electrolyte layer provided between the positive electrode and the negative electrode. The above solid electrolyte is included in at least one of the positive electrode, the negative electrode, and the electrolyte layer.
[0017] The above object and other objects, features, aspects, and advantages will be clarified by the following detailed description of the present invention with reference to the accompanying drawings.
Brief Description of the Drawings
[0018] [Figure 1] It is a longitudinal sectional view showing an all-solid-state secondary battery. [Diagram 2] It is a diagram showing the flow of manufacturing a solid electrolyte. [Diagram 3] It is a diagram showing an X-ray diffraction pattern obtained from a solid electrolyte. [Figure 4] It is a diagram showing the relationship between the molar ratio of LSO (Li2SO4) and lithium ion conductivity. [Diagram 5] It is a diagram showing the flow of another example of manufacturing a solid electrolyte. [Figure 6] FIG. 1 is a graph showing the relationship between the 3b / a value and lithium ion conductivity. [Figure 7] FIG. 1 is a graph showing the relationship between the value of e / (c+e) and lithium ion conductivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] FIG. 1 is a longitudinal sectional view showing an all-solid-state lithium ion secondary battery 1 (hereinafter simply referred to as "all-solid-state secondary battery 1"). The all-solid-state secondary battery 1 has, from the top of FIG. 1, a positive electrode 11, a solid electrolyte layer 13, and a negative electrode 12. That is, the solid electrolyte layer 13 is located between the positive electrode 11 and the negative electrode 12. The solid electrolyte layer 13 also serves as a separator layer. The positive electrode 11 includes a current collector 111 and a positive electrode layer 112. The positive electrode layer 112 includes a positive electrode active material. The negative electrode 12 includes a current collector 121 and a negative electrode layer 122. The negative electrode layer 122 includes a negative electrode active material.
[0020] The positive electrode active material of the positive electrode layer 112 preferably contains a lithium composite oxide. A preferred positive electrode active material is a lithium composite oxide having a layered rock salt structure, such as NCM (Li(Ni,Co,Mn)O2). The positive electrode active material may be another lithium composite oxide, such as NCA (Li(Ni,Co,Al)O2), LCO (LiCoO2), or LNMO (LiNi 0.5 Mn 1.5 Positive electrode layer 112 may be a positive electrode active material, such as LiFePO4, or LFP (LiFePO4) having an olivine structure. In addition to the positive electrode active material, positive electrode layer 112 further includes a solid electrolyte and an electronic conductive assistant (carbon black, etc.) described below. In the present embodiment, positive electrode layer 112 is formed by integrating these materials by applying pressure or heat.
[0021] The negative electrode active material of the negative electrode layer 122 is, for example, LTO (Li4Ti5O 12Examples of the negative electrode layer 122 include compounds such as Nb2TiO7, TiO2 (titanium oxide), graphite, and SiO (silicon monoxide). The negative electrode layer 122 includes a solid electrolyte, which will be described later, in addition to the negative electrode active material. The negative electrode layer 122 may further include an electron conductive assistant (carbon black, etc.). The negative electrode layer 122 in this embodiment is formed by integrating these materials by applying pressure or heat.
[0022] The configurations and materials of the positive electrode 11 and the negative electrode 12 of the all-solid-state secondary battery 1 are not limited to those described above, and various other configurations and materials can be adopted.
[0023] The solid electrolyte layer 13 is made of or contains a solid electrolyte according to the present invention (hereinafter also referred to as "the present solid electrolyte"). The present solid electrolyte is a lithium (Li) ion conductive material. The present solid electrolyte is, for example, a mixture (or synthesis) of a Li3MX6 compound consisting of lithium element (Li), an element (M) that becomes a trivalent cation, and a halogen element (X), and an inorganic salt containing lithium element and sulfur (S) or phosphorus (P). As will be described later, the present solid electrolyte has a composition formula of Li, using values a to f that are greater than 0. a+d M b X c A e O f (wherein M is an element that becomes trivalent as a cation, X is a halogen element, and A is a sulfur element or a phosphorus element), and 0.8c≦(a+3b)≦1.2c and 1.6f≦(d+n×e)≦2.4f (wherein, when A is a sulfur element, n is 4 or 6, and when A is a phosphorus element, n is 5). In addition, preferably, the half-width of a peak detected in the range of 2θ of 20 to 25° in measurement with an X-ray diffractometer using CuKα rays is 0.4° or more. The solid electrolyte has high lithium ion conductivity and high temperature stability. In addition, the solid electrolyte is non-flammable and chemically stable, and does not generate hydrogen sulfide gas, so that an essentially safe all-solid-state secondary battery 1 is provided.
[0024] A preferred example of the solid electrolyte is a mixture of Li3AlF6 (hereinafter referred to as "LAF"), which contains lithium, aluminum, and fluorine, and Li2SO4 (lithium sulfate, hereinafter referred to as "LSO") or LiPO3 (lithium metaphosphate, hereinafter referred to as "LPO"), which are inorganic salts containing lithium and sulfur or phosphorus. The solid electrolyte containing LAF and LSO or LPO has a higher lithium ion conductivity than LAF alone. The reason for this is unclear, but one possible cause is that an interface layer with high lithium ion conductivity is formed at the particle interface between LAF and LSO or LPO by mechanical milling.
[0025] Here, the above-mentioned reference 1, "Li + "(ECS Electrochemistry Letters, 2012, Vol. 1, No. 6, pp. A87-A89) discloses a solid electrolyte in which LAF and LiCl are subjected to mechanical milling. As shown in FIG. 1 of the above-mentioned document 1, this solid electrolyte has a higher lithium ion conductivity than LAF alone. Furthermore, the lithium ion conductivity increases as the temperature increases. However, above 120°C, the lithium ion conductivity decreases significantly. The reason for this is unclear, but one possible cause is the progression of crystallization of LiCl in the temperature range above 120°C. As a result, the lithium ion conductivity of 1.0×10 -4 It becomes difficult to stably obtain lithium ion conductivity exceeding S / cm (siemens per centimeter) at high temperatures.
[0026] In contrast, the present solid electrolyte maintains high lithium ion conductivity even at temperatures exceeding 120°C, for example at 150°C. That is, the present solid electrolyte achieves high temperature stability. The reason for this is not necessarily clear, but one possible reason is that the inorganic salt used in the production of the present solid electrolyte contains sulfur or phosphorus, which inhibits the progress of crystallization of the inorganic salt at temperatures exceeding 120°C. The inorganic salt is preferably LSO (Li2SO4) or LPO (LiPO3). This more reliably inhibits the progress of crystallization of the inorganic salt at temperatures exceeding 120°C and maintains high lithium ion conductivity.
[0027] FIG. 2 is a diagram showing the flow of manufacturing the present solid electrolyte. In the following description, a process of manufacturing the present solid electrolyte by mixing LAF and LSO will be described, but the process is similar when manufacturing the present solid electrolyte by mixing LAF and LPO. First, LAF powder and LSO powder are prepared (step S11). In preparing the LAF powder, for example, commercially available LiF (lithium fluoride) powder and commercially available AlF3 (aluminum fluoride) powder are weighed and mixed. Next, the obtained mixture is heat-treated (for example, at 900° C.), and then pulverized to obtain LAF powder. The LAF powder may be produced by other methods. A commercially available LSO powder is used (similar to the LPO powder). Of course, the LSO powder may be produced by a well-known method (similar to the LPO powder). Step S11 is carried out by using LiF powder, which will be described later. a M b X c and Li d A e O f This is a process of preparing the following:
[0028] Next, the LAF powder and the LSO powder are mixed, and then mechanical milling is performed (step S12). Here, in one example of the mechanical milling, a planetary ball mill is used. In the planetary ball mill, the pot rotates on its axis while the stage on which the pot is placed revolves, so that it is possible to generate very high impact energy. The mechanical milling may be performed using other types of grinders. By the mechanical milling, the powder of the present solid electrolyte to be used for the positive electrode layer 112, the negative electrode layer 122, or the solid electrolyte layer 13 is obtained. In this processing example, the mechanical milling is performed at room temperature, but the conditions such as temperature may be changed as appropriate. In step S12, Li a M b X c and Li d A e O f This is a process of subjecting the above to mechanical milling.
[0029] In step S12, it is preferable that the ratio of the amount of substance of LSO to the total amount of substance of LAF and LSO is greater than 0% and equal to or less than 85%. This more reliably achieves a lithium ion conductivity of the present solid electrolyte higher than that of LAF alone at both room temperature and high temperatures (e.g., 150°C). As shown in the experimental examples described later, in the present solid electrolyte containing LAF and LSO, the ratio of the amount of substance of LSO is 5 to 85%, so that the lithium ion conductivity at 150°C is 1.0 x 10 -4 S / cm or more. In order to further increase the lithium ion conductivity of the present solid electrolyte, the ratio of the substance amount of LSO is preferably 20 to 70%. The same applies when LPO is used instead of LSO.
[0030] FIG. 3 shows an X-ray diffraction (XRD) pattern obtained by measuring the solid electrolyte by powder X-ray diffraction. The XRD pattern in FIG. 3 is obtained from a solid electrolyte (Experimental Example 4 described later) produced by mechanical milling with a substance amount ratio of LSO of 30%. In this measurement, CuKα radiation is used as the radiation source of the X-ray diffraction device. In FIG. 3, the peaks derived from LAF are shown by black circles, and the peaks derived from LSO are shown by black triangles (upside-down triangles). The peaks derived from LAF are peaks that exist in the range of 2θ=21.5°±1.0°, and the peaks derived from LSO are peaks that exist in the range of 2θ=22.5°±1.0°. As shown in FIG. 3, in the solid electrolyte produced by mechanical milling, the peaks derived from LAF and LSO are both broad (similar to the solid electrolytes containing LAF and LPO). This is thought to be because the extremely high impact energy of the mechanical milling process causes the LAF and LSO particles to become finer and partly amorphous, as well as the crystal structure to become disordered due to distortion or dislocation within the crystal, and this phenomenon occurs particularly conspicuously at the particle interface, so that the lithium ion conductivity of the solid electrolyte is thought to be high. Therefore, in order to increase the lithium ion conductivity of the solid electrolyte, it is preferable that the half-width of the peak derived from LAF or the peak derived from LSO detected in the 2θ range of 20 to 25° is 0.4° or more (similarly for solid electrolytes containing LAF and LPO). The upper limit of the half-width is not particularly limited, but is, for example, 3.0°. The solid electrolyte may be amorphous.
[0031] Next, an experimental example of the solid electrolyte will be described. The following experiment was carried out in a glove box or a dry room with a dew point of -40°C or less.
[0032] (Experimental Example 1) As raw materials, commercially available LiF (lithium fluoride) powder and commercially available AlF3 (aluminum fluoride) powder were prepared. Each raw material was weighed and mixed so that LiF:AlF3 was 3:1 (substance ratio). The resulting mixture was heat-treated at 900°C and then pulverized in a mortar to obtain Li3AlF6 (i.e., LAF) powder. As a result, a solid electrolyte powder containing only LAF powder was obtained.
[0033] (Experimental Example 2) In addition to the LAF powder, commercially available Li2SO4 (i.e., LSO) powder was prepared. The LAF:LSO was weighed out to be 90:10 (mass ratio), and mechanically milled using a planetary ball mill to obtain a solid electrolyte powder containing LAF and LSO.
[0034] (Experimental Example 3) A solid electrolyte powder was obtained by carrying out the same treatment as in Experimental Example 2, except that LAF:LSO was weighed out to be 80:20 (substance amount ratio).
[0035] (Experimental Example 4) A solid electrolyte powder was obtained by carrying out the same treatment as in Experimental Example 2, except that LAF:LSO was weighed out to be 70:30 (substance amount ratio).
[0036] (Experimental Example 5) A solid electrolyte powder was obtained by carrying out the same treatment as in Experimental Example 2, except that LAF:LSO was weighed out to be 50:50 (substance amount ratio).
[0037] (Experimental Example 6) A solid electrolyte powder was obtained by carrying out the same treatment as in Experimental Example 2, except that LAF:LSO was weighed out to be 20:80 (substance amount ratio).
[0038] (Experimental Example 7) In addition to the LAF powder, commercially available LiPO3 (i.e., LPO) powder was prepared. The LAF:LPO was weighed out to be 70:30 (mass ratio), and mechanically milled using a planetary ball mill to obtain a solid electrolyte powder containing LAF and LPO.
[0039] <Measurement of lithium ion conductivity> The solid electrolyte powder was placed in a mold consisting of a resin sleeve and upper and lower punches made of SUS (stainless steel), and uniaxial press molding was performed under a pressure of 150 MPa. Lead wires were connected to the upper and lower punches, and impedance measurements were performed at room temperature to 150°C to calculate the lithium ion conductivity.
[0040] <Powder X-ray diffraction measurement> The solid electrolyte powder was analyzed by an X-ray diffractometer (XRD) using CuKα radiation to obtain an X-ray diffraction pattern. The obtained X-ray diffraction pattern was fitted with a pseudo-Voigt peak function (type 1) using data analysis software Origin Pro 2020b, and the half-width of the peak was calculated.
[0041] Table 1 shows some of the compositions of the solid electrolytes of Experimental Examples 1 to 7, their lithium ion conductivities at 150°C, and the half-widths of the strongest peaks in the range of 20 to 25° obtained by X-ray diffraction measurement. In Table 1, Experimental Examples 2 to 7 are examples of the present invention, and Experimental Example 1 is a comparative example. Fig. 4 shows the relationship between the ratio (%) of the amount of LSO to the total amount of LAF and LSO and the lithium ion conductivity at 150°C.
[0042] [Table 1]
[0043] The solid electrolyte powders of Experimental Examples 2 to 6 containing LSO, and the solid electrolyte powder of Experimental Example 7 containing LPO all had higher lithium ion conductivity at 150°C than the solid electrolyte powder of Experimental Example 1 not containing LSO or LPO. In detail, when the ratio of the amount of substance of LSO to the total amount of substance of LAF and LSO was in a relatively low range (for example, 50% or less), the lithium ion conductivity at 150°C increased as the ratio of the amount of substance of LSO increased. When the ratio of the amount of substance of LSO became excessively large, the lithium ion conductivity decreased. However, even in Experimental Example 6, where the ratio of the amount of substance of LSO was 80%, the lithium ion conductivity was 1.1 × 10 -4 S / cm, it is considered that a higher lithium ion conductivity than that of the solid electrolyte powder of Experimental Example 1 is ensured by the ratio of the amount of substance of LSO being greater than 0% and not more than 85%.
[0044] In addition, in Experimental Example 2, in which the ratio of the amount of LSO was 10%, the lithium ion conductivity at 150 °C was 1.2 × 10 -4 Therefore, if the ratio of the amount of LSO is 5 to 85% (i.e., if the molar ratio of LAF to LSO is 95:5 to 15:85), the lithium ion conductivity is approximately 1.0 × 10 -4 It is believed that it is possible to further increase the lithium ion conductivity (for example, to approximately 2.0×10 -4 In order to achieve a lithium ion conductivity of 1.0×10 S / cm or more, the ratio of the amount of LSO is preferably 20 to 70%. In addition, in the solid electrolyte powders of Experimental Examples 2 to 6 and Experimental Example 7, even if a state of 150° C. is maintained for a certain period of time, the lithium ion conductivity is 1.0×10 -4 Thus, the solid electrolyte powder according to the embodiment of the present invention had high temperature stability.
[0045] In addition, in the solid electrolyte powders of Experimental Examples 2 to 5, the XRD patterns had very broad peaks, with the half-width of the strongest peak detected in the range of 20 to 25° being 0.77° to 1.67°.
[0046] <Production of all-solid-state batteries> A positive electrode active material powder, which is NCM, a solid electrolyte powder, and an electronic conductive assistant powder were weighed and mixed to obtain a positive electrode compound powder. A negative electrode active material powder, which is graphite, a solid electrolyte powder, and an electronic conductive assistant powder were weighed and mixed to obtain a negative electrode compound powder. The solid electrolyte powder was placed in a mold consisting of a resin sleeve and upper and lower punches made of SUS, and uniaxial press molding was performed by applying a pressure of 150 MPa. The positive electrode compound powder was placed on top of the pressed solid electrolyte powder and integrated by applying a pressure of 150 MPa. The negative electrode compound powder was placed on the side opposite to the pressed solid electrolyte powder from the positive electrode, and integrated by applying a pressure of 150 MPa. This produced a battery consisting of a positive electrode layer / solid electrolyte layer / negative electrode layer.
[0047] <Charge / discharge test> The battery was placed in a thermostatic chamber at 150°C and a charge / discharge test was carried out. The charge was performed at a current density of 0.4mA / cm 2 The charge was constant current with a cutoff voltage of 4.15 V, and the discharge was at a current density of 0.4 mA / cm 2 The battery was discharged at a constant current with a cutoff voltage of 2.0 V. In the battery using the solid electrolyte powder of Experimental Example 1 (Comparative Example), the discharge capacity was less than 10 mAh / g-NCM (less than 6% of the theoretical capacity). In the battery using the solid electrolyte powder of Experimental Example 5 (Example), the discharge capacity was 47 mAh / g-NCM (about 30% of the theoretical capacity), which was about five times the capacity of the comparative example.
[0048] In the above embodiment, the solid electrolyte is obtained by mechanical milling Li3AlF6 and an inorganic salt such as Li2SO4 or LiPO3, but the solid electrolyte may be produced by mixing a compound containing lithium (Li), an element (M) that becomes a trivalent cation, and a halogen element (X) with any inorganic salt containing lithium and sulfur or phosphorus. In this case, the compound has a composition formula Li where M is aluminum (Al) or another element (typically a metal element) that becomes a trivalent cation, and X is fluorine (F) or another halogen element. a M b Xc (wherein a to c are all greater than 0). Here, Li, M, and X are a monovalent cation, a trivalent cation, and a monovalent anion, respectively, and the above compound is expressed as Li3MX6. In Li3MX6, a+3b=c and a=3b are satisfied. In addition to Li3AlF6, the above compound includes, for example, Li3YF6, Li3LaF6, Li3GaF6, Li3YCl6, Li3YBr6, Li3InCl6, and Li3LaI6.
[0049] Similarly, the above inorganic salts have the formula Li, where A is sulfur or phosphorus. d A e O f (where d to f are all greater than 0). In this case, when A is a sulfur element, Li, A, and O are monovalent cations, tetravalent or hexavalent cations, and divalent anions, respectively, so d+4e=2f or d+6e=2f must be satisfied. When A is a phosphorus element, Li, A, and O are monovalent cations, pentavalent cations, and divalent anions, respectively, so d+5e=2f must be satisfied. In other words, d+n×e=2f must be satisfied (where n is 4 or 6 when A is a sulfur element, and n is 5 when A is a phosphorus element). Examples of the inorganic salts other than Li2SO4 or LiPO3 include Li2SO3 (lithium sulfite), Li3PO4 (lithium orthophosphate), etc.
[0050] In this way, using the values a to f, all of which are greater than 0, compounds consisting of lithium element (Li), an element that becomes a trivalent cation (M), and a halogen element (X) are classified as Li a M b X c Li is an inorganic salt containing lithium and either sulfur or phosphorus. d A e O f When expressed as above, the composition formula of this solid electrolyte is Li a+d M b X c A e Of It is represented by. Also, it is necessary to satisfy a + 3b = c, a = 3b, and d + n×e = 2f (where when A is a sulfur element, n is 4 or 6, and when A is a phosphorus element, n is 5.) under the above-mentioned conditions. Considering measurement errors and the like, it is sufficient if 0.8c ≦ (a + 3b) ≦ 1.2c, 0.8a ≦ 3b ≦ 1.2a, and 1.6f ≦ (d + n×e) ≦ 2.4f are satisfied. Preferably, 0.9c ≦ (a + 3b) ≦ 1.1c, 0.9a ≦ 3b ≦ 1.1a, and 1.8f ≦ (d + n×e) ≦ 2.2f are satisfied. The composition formula is Li a+d M b X c A e O f This solid electrolyte represented by will have high lithium ion conductivity and high temperature stability. As will be described later, when the compound Li a M b X c is not generated, it is not necessary to satisfy 0.8a ≦ 3b ≦ 1.2a.
[0051] As described above, if the ratio of the amount of substance of LSO to the total of the amount of substance of LAF and the amount of substance of LSO is 85% or less, it is more surely realized that the lithium ion conductivity is higher than that of LAF alone. This relationship is considered to be the same for the solid electrolyte of the composition formula Li a+d M b X c A e O f generated from any compound and any inorganic salt. When the ratio of the amount of substance of the above inorganic salt (such as LSO) is 85%, in the above composition formula Li a+d M b X c A e O f e / (c + e) becomes 0.49. Therefore, in the solid electrolyte of the composition formula Li a+d M b X c A e O f by satisfying 0 < e / (c + e) ≦ 0.5, in this solid electrolyte, Li a M b X cIt is possible to more reliably achieve a higher lithium ion conductivity than the single substance. As mentioned above, a to f are values greater than 0, and the solid electrolyte is Li d A e O f Includes.
[0052] In order to increase the lithium ion conductivity, the ratio of the amount of the above inorganic salts is set to 5 to 85%, and the composition formula Li a+d M b X c A e O f It is preferable that the ratio of the amount of substance of the inorganic salt is set to 20 to 70% and the lithium ion conductivity is further increased by using the composition formula Li a+d M b X c A e O f It is preferable that e / (c+e) satisfies 0.04≦e / (c+e)≦0.28.
[0053] Preferably, Li d A e O f is Li2SO4 or LiPO3 (i.e., LSO or LPO), which more reliably maintains high lithium ion conductivity at high temperatures. d A e O f If is LSO, the formula Li a+d M b X c A e O f In the formula, A is a sulfur element, and d=2e is satisfied. Taking into account measurement errors, etc., it is sufficient that 0.8d≦2e≦1.2d is satisfied, and preferably 0.9d≦2e≦1.1d is satisfied. d A e O f If LPO, the formula Li a+d M b X c A e O fIn the formula, A is a phosphorus element, and d=e is satisfied. In consideration of measurement errors, it is sufficient that 0.8d≦e≦1.2d is satisfied, and preferably 0.9d≦e≦1.1d is satisfied. In addition, it is preferable that Li a M b X c is Li3AlF6 (i.e., LAF). In other words, the composition formula Li a+d M b X c A e O f In the above formula, M is an aluminum element and X is a fluorine element, whereby high lithium ion conductivity is more reliably achieved.
[0054] As mentioned above, the composition formula of this solid electrolyte is Li a+d M b X c A e O f For example, when LAF and LSO are mixed, the composition formula is Li a+d Al b F c S e O f In addition, when LAF and LPO are mixed, the composition formula is expressed as Li a+d Al b F c P e O fIt is represented by. When confirming whether an unknown solid electrolyte is this solid electrolyte, chemical analysis is performed on the unknown solid electrolyte to check whether the constituent elements are Li, M, X, A, O (where M is an element with a trivalent cation, X is a halogen element, and A is a sulfur element or a phosphorus element).) If the constituent elements are Li, M, X, A, O, and the values a to f of the molar ratios of the constituent elements are all greater than 0, 0.8c ≤ (a + 3b) ≤ 1.2c, and 1.6f ≤ (d + n × e) ≤ 2.4f (where n is 4 or 6 when A is a sulfur element and n is 5 when A is a phosphorus element), it can be said that the unknown solid electrolyte is this solid electrolyte. Also, when 0 < e / (c + e) ≤ 0.5 is satisfied, it can be said that the ratio of the amount of substance of the above inorganic salt (such as LSO) to the total amount of substance of the above compound (such as LAF) and the above inorganic salt is 85% or less.
[0055] For example, Li, Al, S, and P can be quantified by an ICP-emission spectroscopic analyzer. For F, it can be quantified by an ion chromatograph. For O (oxygen), it can be quantified by oxygen-nitrogen gas analysis. When this solid electrolyte contains an element M other than Al and an element X other than F, a measurement method capable of quantifying the element M and the element X is appropriately selected.
[0056] In the above processing example, the case where LiF and AlF3 are mixed at a molar ratio of 3:1 to generate Li3AlF6 (i.e., LAF) and then Li3AlF6 and Li2SO4 (or LiPO3) are mechanically milled was described. However, it is also possible to mechanically mill LiF, AlF3, and Li2SO4 (or LiPO3) without generating Li3AlF6.
[0057] 5 is a diagram showing the flow of another example of manufacturing the present solid electrolyte. In this manufacturing example, LiF powder, AlF powder, and Li2SO4 (or LiPO3) powder are prepared (step S21). Then, the LiF powder, AlF3 powder, and Li2SO4 (or LiPO3) powder are mixed, and then mechanical milling is performed (step S22).
[0058] In this case, the ratio of the amount of substance of LiF to AlF3 may be other than 3:1. The ratio of the amount of substance of LiF to the total amount of substance of LiF, AlF3, and Li2SO4 is, for example, 10% or more and 80% or less, preferably 30% or more and 70% or less. The ratio of the amount of substance of AlF3 is, for example, 5% or more and 60% or less, preferably 10% or more and 50% or less. The ratio of the amount of substance of Li2SO4 is, for example, 2% or more and 50% or less, preferably 10% or more and 40% or less. By the above process, the powder of the present solid electrolyte having high lithium ion conductivity and high temperature stability is obtained. The same applies when LiPO3 is used instead of Li2SO4.
[0059] Here, the ratio of the amount of substance of Li, Al, and F in the mixture prepared in step S21 when only LiF and AlF3 are mixed is represented as a:b:c (where a to c are values greater than 0). In this case, Li, Al, and F are monovalent cations, trivalent cations, and monovalent anions, respectively, so a+3b=c is satisfied. Taking into consideration measurement errors and the like, 0.8c≦(a+3b)≦1.2c is satisfied. On the other hand, unlike the case where Li3AlF6 is generated in advance, the ratio of the amount of substance of LiF and AlF3 is not limited to 3:1, so a=3b is not necessarily satisfied. In other words, even if 0.8a≦3b≦1.2a is not satisfied, it is possible to obtain the present solid electrolyte having high lithium ion conductivity and high temperature stability.
[0060] Next, experimental examples of producing the present solid electrolyte by mixing LiF, AlF3, and Li2SO4 will be described with reference to Table 2. Experimental Examples 8 to 17 in Table 2 are examples of the present invention.
[0061] [Table 2]
[0062] (Experimental Example 8) Commercially available LiF powder, commercially available AlF3 powder, and commercially available Li2SO4 powder were prepared. LiF:AlF3:Li2SO4 was weighed out to be 60:20:20 (substance ratio), and mechanical milling was performed using a planetary ball mill to obtain a solid electrolyte powder containing LiF, AlF3, and Li2SO4. Thereafter, the lithium ion conductivity was measured in the same manner as in the above-mentioned "Measurement of lithium ion conductivity". In Experimental Example 8, the lithium ion conductivity at 150°C was 4.1 x 10 -4 S / cm, and the ion conduction path of the comparative example, Experimental Example 1 (5.0×10 -5 The mass ratio of LiF, AlF3, and Li2SO4 in Experimental Example 8 was the same as in Experimental Example 5 described above, but it differed from Experimental Example 5 in that Li3AlF6 was not generated in advance.
[0063] (Experimental Examples 9-17) In Experimental Examples 9 to 17, the same treatment as in Experimental Example 8 was carried out to obtain solid electrolyte powders, except that LiF:AlF3:Li2SO4 was weighed out to have the mass ratio shown in Table 2. Thereafter, the lithium ion conductivity was measured. In Experimental Examples 9 to 17, the mass ratio of LiF to AlF3 was different from 3:1, but the lithium ion conductivity at 150°C was higher than that of Experimental Example 1 in all cases.
[0064] As described above, when the mass ratio of Li, Al, and F in a mixture of LiF and AlF3 is expressed as a:b:c, even if a=3b is not satisfied (i.e., when the mass ratio of LiF and AlF3 is different from 3:1), a solid electrolyte having high lithium ion conductivity is realized. In fact, the solid electrolyte powders of Experimental Examples 8 to 17 maintained high lithium ion conductivity and obtained high temperature stability even when held at 150°C for a certain period of time.
[0065] Next, the preferred range such as 3b / a will be described. Here, for Experimental Examples 8 to 17, among LiF, AlF3, and Li2SO4 used in the production of the solid electrolyte, the molar ratios of Li, Al, F in the mixture of LiF and AlF3, and Li, S, O in Li2SO4 are represented as a:b:c:d:e:f. For Experimental Examples 1 to 6, the molar ratios of Li, Al, F in Li3AlF6 used in the production of the solid electrolyte, and Li, S, O in Li2SO4 are represented as a:b:c:d:e:f. a to f are values greater than 0.
[0066] Figure 6 is a diagram showing the relationship between the value of 3b / a in Experimental Examples 1 to 6, 8 to 17 and the lithium ion conductivity at 150°C. In Figure 6, the ion conductivities of Experimental Examples 1 to 6 are plotted as circles, the ion conductivities of Experimental Examples 8 to 17 are plotted as squares, and the ion conductivity in Experimental Example 1, which is a comparative example, is shown by line L1 (the same applies in Figure 7 described later). From Figure 6, it is clear that even outside the range of 0.8 ≤ 3b / a ≤ 1.2 (that is, 0.8a ≤ 3b ≤ 1.2a), this solid electrolyte has high lithium ion conductivity. To more surely achieve high lithium ion conductivity in this solid electrolyte, it is preferable to satisfy 0.1 ≤ 3b / a ≤ 10 (that is, 0.1a ≤ 3b ≤ 10a). 3b / a is more preferably 0.5 or more, and even more preferably greater than 1.0. 3b / a is more preferably 8.5 or less, and even more preferably 6.0 or less.
[0067] Figure 7 is a diagram showing the relationship between the value of e / (c + e) in Experimental Examples 1 to 6, 8 to 17 and the lithium ion conductivity at 150°C. As described above, the value of e / (c + e) is related to the mixing ratio of Li2SO4. From Figure 7, it can be seen that by satisfying 0 < e / (c + e) ≤ 0.5, high lithium ion conductivity can be more surely achieved. To further increase the lithium ion conductivity, it is preferable to satisfy 0.04 ≤ e / (c + e) ≤ 0.28.
[0068] In the production of the solid electrolyte of FIG. 5, as described above, the present solid electrolyte is obtained by mechanical milling LiF, AlF3, and Li2SO4, but the raw materials of the present solid electrolyte are not limited to LiF, AlF3, and Li2SO4 (or LiPO3). The present solid electrolyte may be produced by mixing a first compound which is LiX, a second compound which is MX3, and a third compound which is Li, A, and O, where X is any halogen element, M is any element which becomes trivalent as a cation, and A is sulfur or phosphorus element. In this case, in step S21 of FIG. 5, the first compound, the second compound, and the third compound are prepared. In step S22, the first compound, the second compound, and the third compound are mechanically milled to obtain the present solid electrolyte.
[0069] When the ratio of the amounts of substances of Li, M, and X in the mixture of the first and second compounds, and Li, A, and O in the third compound are expressed as a:b:c:d:e:f using values a to f greater than 0, the mixture satisfies 0.8c≦(a+3b)≦1.2c as described above. In addition, the third compound satisfies 1.6f≦(d+n×e)≦2.4f as described above (wherein, when A is a sulfur element, n is 4 or 6, and when A is a phosphorus element, n is 5). The first compound LiX is, for example, LiCl, LiBr, etc., in addition to LiF. The second compound MX3 is, for example, YF3, LaF3, GaF3, etc., in addition to AlF3. The third compound Li d A e O f In addition to Li2SO4 or LiPO3, for example, Li2SO3 (lithium sulfite), Li3PO4 (lithium orthophosphate), etc.
[0070] The solid electrolyte shown in FIG. 5 was also produced using the formula Li a+d M b X c A e O fThe present solid electrolyte represented by [the formula] has high lithium ion conductivity and high temperature stability. Further, it is preferable that 0 < e / (c + e) ≦ 0.5 is satisfied, whereby high lithium ion conductivity can be more surely realized. The mixing ratio of the first compound LiX and the second compound MX3 is not particularly limited, but in order to more surely obtain high lithium ion conductivity, it is preferable that 0.1a ≦ 3b ≦ 10a is satisfied.
[0071] Various modifications are possible for the present solid electrolyte, the method for producing the present solid electrolyte, and the battery.
[0072] The present solid electrolyte may contain impurities, and the components represented by the composition formula Li a+d M b X c A e O f only need to be contained as main components. The main component is the component having the largest mass ratio among the components contained in the solid electrolyte. The mass ratio of the main component in the solid electrolyte is preferably 80% by mass or more, more preferably 90% by mass or more. The present solid electrolyte may be mixed with other substances (which may contain Li) and used as an electrolyte material. The mass ratio of the present solid electrolyte in the electrolyte material is preferably 50% by mass or more, more preferably 60% by mass or more, and still more preferably 70% by mass or more.
[0073] In the X-ray diffraction pattern obtained from the present solid electrolyte, the full width at half maximum of the peak detected in the range of the diffraction angle 2θ of 20 to 25° may be less than 0.4°.
[0074] The solid electrolyte layer 13 may contain substances other than the present solid electrolyte. The present solid electrolyte used in the all-solid-state secondary battery 1 does not necessarily have to be contained in all of the positive electrode 11, the negative electrode 12, and the solid electrolyte layer 13, and may be contained in at least one of the positive electrode 11, the negative electrode 12, and the solid electrolyte layer 13. The present solid electrolyte may be used in batteries other than all-solid-state secondary batteries, and may also be used for applications other than batteries. The production of the present solid electrolyte may be carried out by means other than mechanical milling treatment.
[0075] The configurations in the above-described embodiment and each of the modified examples may be combined as appropriate as long as they are not mutually inconsistent.
[0076] Although the invention has been particularly illustrated and described, it is to be understood that the above description is illustrative and not restrictive, and therefore numerous modifications and variations are possible without departing from the scope of the invention. [Explanation of symbols]
[0077] 1. All-solid-state lithium-ion secondary battery 11 Positive electrode 12 Negative electrode 13 Solid electrolyte layer S11, S12, S21, S22 steps
Claims
1. A solid electrolyte, With values a to f greater than 0, the composition formula is Li a+d M b X c A e O f (wherein M is an element that becomes trivalent as a cation, X is a halogen element, and A is a sulfur element or a phosphorus element), The following conditions are satisfied: 0.8c≦(a+3b)≦1.2c, and 1.6f≦(d+n×e)≦2.4f (wherein, when A is elemental sulfur, n is 4 or 6, and when A is elemental phosphorus, n is 5).
2. The solid electrolyte according to claim 1, In the composition formula, 0<e / (c+e)≦0.5 is satisfied.
3. The solid electrolyte according to claim 1 or 2, In the above composition formula, 0.1a≦3b≦10a is satisfied.
4. 4. The solid electrolyte according to claim 1, In the composition formula, A is a sulfur element and 0.8d≦2e≦1.2d is satisfied, or A is a phosphorus element and 0.8d≦e≦1.2d is satisfied.
5. 5. The solid electrolyte according to claim 1 , In the above composition formula, A is elemental sulfur and n is 6.
6. 6. A solid electrolyte according to claim 1, In the above composition formula, M is an aluminum element, and X is a fluorine element.
7. 7. A solid electrolyte according to claim 1, In measurement using an X-ray diffractometer using CuKα radiation, the half-width of a peak detected in the 2θ range of 20 to 25° is 0.4° or more.
8. A method for producing a solid electrolyte, comprising the steps of: a) Using values a to f greater than 0, the composition formula is Li a M b X c And Li d A e O f (wherein M is an element which becomes trivalent as a cation, X is a halogen element, A is elemental sulfur or elemental phosphorus, a to f satisfy 0.8c≦(a+3b)≦1.2c and 1.6f≦(d+n×e)≦2.4f, and when A is elemental sulfur, n is 4 or 6, and when A is elemental phosphorus, n is 5); b) Li a M b X c and Li d A e O f and subjecting the resultant to mechanical milling. Equipped with In the step b), Li a M b X c and Li d A e O f The amount of Li in the total d A e O f The ratio of the amount of substance is 85% or less.
9. A method for producing a solid electrolyte, comprising the steps of: a) a first compound which is LiX; and 3 and a third compound consisting of Li, A and O (wherein X is a halogen element, M is an element that becomes trivalent as a cation, and A is a sulfur element or a phosphorus element); b) subjecting the first compound, the second compound and the third compound to a mechanical milling process; Equipped with In the step a), when the substance amount ratios of Li, M, and X in the mixture of the first compound and the second compound, and Li, A, and O in the third compound are expressed as a:b:c:d:e:f using values a to f greater than 0, 0.8c≦(a+3b)≦1.2c and 1.6f≦(d+n×e)≦2.4f (wherein, when A is elemental sulfur, n is 4 or 6, and when A is elemental phosphorus, n is 5) are satisfied, and 0<e / (c+e)≦0.5 is further satisfied.
10. A method for producing the solid electrolyte according to claim 8 or 9, In the step a), 0.1a≦3b≦10a is satisfied.
11. A method for producing a solid electrolyte according to any one of claims 8 to 10, comprising the steps of: A is a sulfur element and 0.8d≦2e≦1.2d is satisfied, or A is a phosphorus element and 0.8d≦e≦1.2d is satisfied.
12. A method for producing a solid electrolyte according to any one of claims 8 to 11, comprising the steps of: A is elemental sulfur and n is 6.
13. A method for producing a solid electrolyte according to any one of claims 8 to 12, comprising the steps of: M is an aluminum element and X is a fluorine element.
14. A battery, A positive electrode and A negative electrode; an electrolyte layer provided between the positive electrode and the negative electrode; Equipped with The solid electrolyte according to any one of claims 1 to 7 is contained in at least one of the positive electrode, the negative electrode, and the electrolyte layer.
Citation Information
Patent Citations
Compositions suitable for electrochemical cells
JP2002522872A
Polyurethane-derived electrolyte systems for electrochemical cells
JP2014532962A
Battery and manufacturing method thereof
JP2022132739A